Effect of sex difference on platelet aggregation using an optical method in healthy subjects - BEYAN, C.; KAPTAN, K.; IFRAN, A.; SAVAŞÇI, S.; ÖZTÜRK, Y.; ÖKMEN, B. (Clinical and laboratory haematology, 2006)
Summary There are many studies reporting conflicting results of sex differences on various platelet functions. The purpose of this study was to investigate whether sex differences could affect platelet aggregation results using an optical method in healthy subjects. A total of 42 subjects, 21 males and 21 females, were included in the study. Platelet aggregation was induced by adenosine diphosphate (ADP; 5 μm), collagen (2 μg/ml), and epinephrine (10 μm). Optical aggregation was performed using a turbidometric method. In all platelet aggregation tests ADP, collagen and epinephrine were studied; there was no significant difference between females and males in platelet aggregation amplitudes and slopes. As a result, sex difference does not affect platelet aggregation performed with this optical method in healthy subjects. This result supports that there is no need for sex differentiation while composing control groups in platelet aggregation studies using the optical method.